Food safety practice and its associated factors among food handlers working in food and drinking establishments in Hargeisa, Somaliland - Mohamed Mussa Abdilahi; Jonah Kiruja; Abdisamad Shukri Ismail; Soheir H. Ahmed; Faisal Nooh; Ayanle Suleiman Ahmed; Abdiqathar Rashid Kulmie (BMC Public Health)
Abstract Background The World Health Organization reports that 600 million cases of food-borne illnesses occur every year. Additionally, it is estimated that upto 30% of people in developed countries experience food-borne illnesses annually, while developing countries suffer around 2 million deaths from these diseases each year. Inadequate sanitation and challenges in maintaining proper food handling practices are the major contributing factors of food-borne illnesses in developing countries including Somaliland. Aims The aim of the study was to assess food safety practices and its associated factors among food handlers working in food and drinking establishments in Hargeisa, Somaliland. Methods A community-based cross-sectional study was conducted from September 20 to October 20, 2024, involving 306 randomly selected food handlers in Hargeisa, Somaliland. Data was collected using a structured questionnaire and analyzed with SPSS version 22. Descriptive analysis summarized respondents’ socio-demographic characteristics, while bivariate and multivariable analyses examined relationships in the data. Independent variables with a p-value below 0.25 were included in multivariable logistic regression to identify significant factors, using adjusted odds ratios (AORs) and a 95% confidence interval (CI), with a significance threshold of p < 0.05. Results In this study, a total of 306 food handlers participated. The majority (85.3%) of food handlers was males and 84% had non-formal education. The prevalence of poor food safety practices among food handlers was at 52.3%. Lack of food safety training (AOR = 0.172; 95% CI: 0.070, 0.420), less working experience (AOR = 1.757; 95% CI: 1.026, 3.009), lack of appropriate water storage equipment (AOR = 0.602; 95% CI: 0.364, 0.996), lack of regular sanitary inspection (AOR = 1.691; 95% CI: 1.028, 2.783), and poor knowledge (AOR = 0.589; 95% CI: 0.353, 0.983) were statistically associated with poor food safety practices. Conclusion The study found low level of poor food safety practices; attributed to factors like food handler training, work experience, water storage equipment, sanitation inspections, and knowledge. However, enhancing food handling practices, particularly training is crucial to minimize food-borne diseases and promote optimal food safety practices.